Strikes through the Prism of Duties: Is There a Fundamental Duty to Strike under the Indian Constitution? - DAM, Shubhankar (Institutional Knowledge at Singapore Management University, 2004)
Much of the debates on the legality of strikes under the Indian Constitution has been on the issue of a right to strike. This paper argues that the constitutionality of strikes may be analysed through the prism of duties, i.e. fundamental duties under Part IVA of the Constitution. Strikes were an integral part of the ideals that inspired India's national struggle against imperialism. And, in this sense, when article 51A exhorts Indians to cherish and follow the noble ideals that inspired our freedom struggle, it includes a fundamental duty to strike. Invoking the philosophy of Mahatma Gandhi, the paper argues that the constitutionality of strikes under Part IVA is dependent on five essential conditions. A duty to strike is constitutional only and only if the five conditions are satisfied.